Pengelolaan Lansekap Parkir Obyek Wisata Ceking Kecamatan Tegallalang Kabupaten Gianyar Provinsi Bali - PARIS, I KADEK; SUGIANTHARA, ANAK AGUNG GEDE; GUNADI, I GUSTI ALIT (Jurnal Arsitektur Lansekap; Vol.2, No.2, Oktober 2016, 2016)
ABSTRACT The Management of Parking Lanscape in the Tourist Destination of Ceking, Sub-District of Tegallalang, Gianyar Regency, Province of Bali. This study aims to Know the parking area management system implemented in Heritage Ceking terms of the Landscape Architecture and analyze the factors that affect the maintenance of parking area attractions skinny. The method used in this research is survey method with interview techniques (interviews), techniques for distributing questionnaires and observation techniques (observation). Data sought is the primary and secondary data. Primary data in this study were obtained from internal interviews (worker object Ceking Travel, landowners and visitors). Secondary data were obtained from the Internet and books or other reference is the village of Tegallalang profile. The results showed that the management system is applied to the parking area manager Heritage Ceking during the past year, namely by forming BPOWC (Object Travel Agency business Ceking), shelter under Pekraman Tegallalang village. Standard operating procedures (SOP) management of Heritage Ceking governed by an organizational structure through Paruman between BPOWC with Pekraman Tegallalang village. Factors affecting the maintenance of parking areas at Heritage Ceking including internal and external factors. Internal factors including site conditions, operational management of the landscape, such as the management of the park, hard materials and planning by managers. External factors include the user's perception of the existence Heritage Area Parking Ceking including specification (beauty, cleanliness, garden arrangement, crop conditions, the condition of the hard material, comfort and safety). Hasil pengelolaan Area Parkir Obyek Wisata Ceking tergolong baik dengan skor rata-rata 69,3%, sesuai dengan Skala Lekert.